PEMBERDAYAAN MASYARAKAT DESA SUKANAGALIH, CIANJUR MELALUI EDUKASI BUDIDAYA DAN PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) DALAM MENANGANI MASALAH KESEHATAN SEHARI-HARI SECARA MANDIRI - Ernie Halimatushadyah; Agnes Yuliana; Ratnayani Ratnayani; Syafrima Wahyu; Liyna Fatimah; Muhamad Ardiansyah; Edvan Duta Zulham; Julia Dwi Rahmadianti (Universitas Mataram, 2025)
Sukanagalih Village, located in Pacet Subdistrict, Cianjur Regency, is one of the fostered villages of Binawan University with significant potential in the development and utilization of Family Medicinal Plants (TOGA) and local food resources. However, this potential has not been optimally harnessed due to the community’s limited knowledge regarding the types of medicinal plants, proper processing methods, usage guidelines, and the concept of balanced nutrition. This community service program aimed to enhance the community’s self-reliance in maintaining family health through education on the use of TOGA and local food. The implementation method consisted of five main stages: preparation, education, training and technology application, mentoring and cadre development, as well as evaluation and reporting. The activities involved posyandu (integrated health post) cadres, local residents, and youth using participatory and practical approaches. Evaluation was conducted using pre-tests and post-tests to measure knowledge improvement, as well as direct observation of the community's practice in cultivating TOGA. The results indicated a significant increase in knowledge and skills among participants. Additionally, the establishment of a greenhouse and hydroponic training provided effective solutions to limited land availability. In conclusion, the program proved effective in improving health literacy, cultivation skills, and empowering the community sustainably through the utilization of local potential. This model is expected to be replicable in other regions with similar characteristics.